A carbon nanotube-titanium nitride composite nanofluid, its preparation method and application
By preparing carbon nanotube-titanium nitride composite nanofluids, the problems of narrow spectral coverage and low photothermal conversion efficiency of single-component nanofluids were solved, achieving improved full-spectrum absorption and excellent dispersion stability, making it suitable for direct absorption solar collectors.
Patent Information
- Application Number
- CN202611099727.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-11-06
AI Technical Summary
Existing single-component nanofluids have narrow spectral coverage and limited photothermal conversion efficiency. Furthermore, composite nanofluids are prone to nanoparticle aggregation and sedimentation, resulting in poor dispersion stability and severe degradation of light absorption performance under long-term irradiation, which limits the application of direct absorption solar collectors.
A composite nanofluid of carbon nanotubes and titanium nitride was prepared by surface modification with oleic acid as a dispersant. The preparation method included raw material pretreatment, base solution preparation, mixing and stirring, and light-protected standing to form a stable composite nanofluid. The carbon nanotubes and titanium nitride complement each other in the ultraviolet-near infrared spectrum absorption, and the local surface plasmon resonance effect of titanium nitride is used to enhance the absorption of full-spectrum sunlight.
It achieves full-spectrum synergistic light absorption, improves solar weighted absorptivity, exhibits excellent dispersion stability, and enhances photothermal conversion efficiency. The fluid efficiency is improved by 3.8%~7.9% under 60 minutes of irradiation, making it suitable for direct absorption solar collector photothermal conversion systems.
Smart Images

Figure CN123042684A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofluid heat transfer technology, and more specifically, to a carbon nanotube-titanium nitride composite nanofluid, its preparation method, and its application. Background Technology
[0002] Solar thermal power generation is one of the core technological pathways for the large-scale utilization of renewable energy. Direct absorption solar collectors (DASCs) abandon traditional metal heat-absorbing coatings. Compared to traditional collectors that rely on black surface coatings to absorb radiation energy, DASCs allow the working fluid to directly absorb solar energy in bulk, effectively reducing energy loss during heat transfer. However, conventional working fluids such as water, ethylene glycol, and other fluids generally have weak solar energy absorption capabilities, greatly limiting the operating efficiency of DASCs. Against this backdrop, the development of novel working fluids has become a research hotspot in this field. Using nanofluids as the heat-collecting working fluid to directly absorb sunlight offers advantages such as small heat exchange temperature difference, high photothermal coupling efficiency, and simplified system structure, making it a core research direction for next-generation high-efficiency solar thermal collector technology. Nanofluids prepared by dispersing nanoparticles in a base liquid can effectively improve the light absorption capacity and heat transfer performance of the working fluid in DASCs.
[0003] Currently, mainstream photothermal nanofluids are divided into two categories: carbon-based nanofluids and plasma-enhanced metal / metal nitride nanofluids. Existing single-component nanofluids suffer from narrow spectral coverage and limited improvement in photothermal conversion efficiency; simple physical mixtures of nanofluids are prone to nanoparticle aggregation and sedimentation, resulting in poor dispersion stability and severe degradation of light absorption performance under long-term irradiation. The lack of a binary composite nanofluid preparation process that simultaneously achieves broad spectral absorption, long-term dispersion stability, low cost, and high photothermal conversion efficiency limits the practical application of DASC systems. Summary of the Invention
[0004] To address the issues of narrow spectral coverage and limited photothermal conversion efficiency of existing single-component fluids, this invention provides a carbon nanotube-titanium nitride composite nanofluid, its preparation method, and its applications.
[0005] In a first aspect, the present invention provides a carbon nanotube-titanium nitride composite nanofluid, comprising:
[0006] Carbon nanotubes, titanium nitride (TiN), a dispersant, and a base liquid are used. The dispersant is modified on the surface of the carbon nanotubes and the titanium nitride, and the mass ratio of the carbon nanotubes to the titanium nitride is 2:1~4.
[0007] Optionally, the mass ratio of the carbon nanotubes to the titanium nitride is 2:2.
[0008] Optionally, the concentration of the carbon nanotubes is 10-20 mg / L, the concentration of the titanium nitride is 5-20 mg / L, and the concentration of the dispersant is 15-20 mg / L.
[0009] Optionally, the carbon nanotubes are single-walled carbon nanotubes, double-walled carbon nanotubes, or multi-walled carbon nanotubes; the base liquid is an oily liquid; and the dispersant is oleic acid, stearic acid, or ricinoleic acid.
[0010] Optionally, the carbon nanotubes are multi-walled carbon nanotubes (MWCNTs).
[0011] Optionally, the dispersant is oleic acid.
[0012] Optionally, the oily liquid is a heat transfer oil with an operating temperature of 250°C or higher.
[0013] Optionally, the oily liquid is a heat transfer oil with an operating temperature of 250~350℃.
[0014] Optionally, the heat transfer oil is T66 type heat transfer oil.
[0015] Optionally, the carbon nanotubes have a strip-like structure, with an outer diameter of 10-20 nm and a length of 10-30 μm.
[0016] Optionally, the titanium nitride is in the form of spherical particles with a particle size of 10-20 nm.
[0017] Secondly, the present invention provides a method for preparing carbon nanotube-titanium nitride composite nanofluids, comprising the following steps:
[0018] Carbon nanotube powder and titanium nitride particles are prepared for use after surface treatment;
[0019] The dispersant is dissolved in the base liquid to obtain an oil-phase dispersion substrate;
[0020] The surface-treated carbon nanotube powder is added to the oil-phase dispersion substrate and mixed and stirred to obtain a carbon nanotube mother liquor;
[0021] Titanium nitride particles were added to the carbon nanotube mother liquor, and after mixing and stirring, the mixture was allowed to stand in the dark to remove bubbles, thus obtaining a composite nanofluid.
[0022] Optionally, the carbon nanotube powder is added to the oil-phase dispersion substrate, stirred at a speed of 500-1000 r / min for 30-60 min, and then ultrasonically dispersed in a water bath for 40-60 min.
[0023] Optionally, the surface treatment includes: the carbon nanotube powder being washed with alcohol and dried; and the titanium nitride particles being washed with water and dried.
[0024] Optionally, the carbon nanotube powder is ultrasonically cleaned with anhydrous ethanol and then vacuum dried at 60°C for 12 hours; the titanium nitride particles are washed with deionized water and then vacuum dried at 60°C.
[0025] Optionally, the titanium nitride particles are added to the carbon nanotube mother liquor in a concentration gradient.
[0026] Optionally, the titanium nitride particles are added to the carbon nanotube mother liquor in five separate additions. Specifically, the amount added in each of the five additions is the same.
[0027] Optionally, after the titanium nitride particles are added to the carbon nanotube mother liquor and mixed and stirred, they are subjected to water bath ultrasonic dispersion and probe ultrasonic dispersion, and then subjected to light-protected static degassing. The ultrasonic power of the water bath ultrasonic dispersion and the probe ultrasonic dispersion is 600~800W, and the water bath temperature of the water bath ultrasonic dispersion is 45~50℃.
[0028] Optionally, the ultrasonic dispersion time in the water bath is 20-30 minutes; the ultrasonic dispersion time of the probe is 20-30 minutes.
[0029] Thirdly, the present invention provides an application of carbon nanotube-titanium nitride composite nanofluid in a direct absorption solar collector photothermal conversion system.
[0030] To address the problem of narrow spectral coverage and limited photothermal conversion efficiency of existing single-component fluids, this invention offers the following advantages:
[0031] 1. In this invention, carbon nanotubes and titanium nitride are combined to achieve complementary absorption in the ultraviolet-near-infrared spectrum. The local surface plasmon resonance effect of titanium nitride is used to synergistically enhance the absorption of full-spectrum sunlight. Oleic acid is used to modify the surface of carbon nanotubes and titanium nitride, so that the finished composite nanofluid has no obvious precipitation after standing for 7 days, the absorbance decreases by less than 5%, and the dispersion stability is excellent.
[0032] 2. The composite nanofluid of this invention achieves a solar weighted absorptivity of 94.89% under a 2cm optical path, and its 60-minute irradiation photothermal conversion efficiency is 3.8%~7.9% higher than that of a single fluid containing MWCNTs. It balances surface heat absorption and deep heat storage, resulting in lower heat loss.
[0033] 3. The composite nanofluid of this invention has a simple preparation process, low raw material cost, and can be mass-produced. It is suitable for direct absorption solar collector photothermal conversion systems. Attached Figure Description
[0034] Figure 1 This is a physical image of the carbon nanotube-titanium nitride composite nanofluid of the present invention.
[0035] Figure 2 This is a TEM image of the fluid in this invention;
[0036] Figure 3 The absorbance of the fluid in this invention;
[0037] Figure 4 The fluid transmittance of this invention;
[0038] Figure 5 This refers to the fluid spectral absorption density of the present invention.
[0039] Figure 6 The fluid solar weighted absorptivity of this invention;
[0040] Figure 7 The temperature of the bottom fluid in the fluid of this invention changes with irradiation time;
[0041] Figure 8 The temperature of the middle fluid in the fluid of this invention changes with irradiation time;
[0042] Figure 9 The temperature of the top fluid in the fluid of this invention changes with irradiation time;
[0043] Figure 10 A comparison of the temperature changes of the fluid at the top, middle, and bottom of the fluid after 1 hour of illumination, for the present invention;
[0044] Figure 11 The temperature field distribution of the collector during the photothermal conversion of the fluid in Comparative Example 2 is shown.
[0045] Figure 12 The temperature field distribution of the collector during the photothermal conversion of the fluid in Comparative Example 1 is shown.
[0046] Figure 13 The temperature field distribution diagram of the solar collector during the photothermal conversion of the fluid in Example 1;
[0047] Figure 14 Temperature field distribution diagram of the collector during photothermal conversion of fluid in Example 2;
[0048] Figure 15 Temperature field distribution diagram of the solar collector during photothermal conversion of fluid in Example 3;
[0049] Figure 16 Temperature field distribution diagram of the collector during photothermal conversion of fluid in Example 4;
[0050] Figure 17 The efficiency of mixed MWCNT-TiN nanofluid collectors with different TiN concentrations varies with irradiation time;
[0051] Figure 18A comparison of the efficiency of mixed MWCNT-TiN nanofluid collectors with different TiN concentrations after irradiation for 60 min;
[0052] Figure 19 The variation of the solar collector's photothermal conversion efficiency with fluid depth after 20 minutes of irradiation is shown. Detailed Implementation
[0053] The invention will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are described merely to enable those skilled in the art to better understand and thus implement the invention, and are not intended to imply any limitation on the scope of the invention.
[0054] As used herein, the term "comprising" and its variations are to be interpreted as open-ended terms meaning "including but not limited to". The terms "one embodiment" and "an embodiment" are to be interpreted as "at least one embodiment". The term "another embodiment" is to be interpreted as "at least one other embodiment". These terms are primarily used to better describe this application and its embodiments and are not intended to limit the indicated components to having a particular orientation, or being constructed and operated in a particular orientation. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances. Furthermore, the terms "first", "second", etc., are primarily used to distinguish different components (the specific types may be the same or different) and are not intended to indicate or imply the relative importance and number of the indicated components. Unless otherwise stated, "a plurality of" means two or more.
[0055] Existing single-type nanofluids typically struggle to achieve full-spectrum coverage. Hybrid nanofluids, prepared by combining two or more nanoparticles, can better match a broad spectrum and achieve stronger solar energy absorption, thus becoming an important technological path to improve the performance of solar collectors. Multi-walled carbon nanotubes still possess excellent spectral absorption capabilities even at extremely low doping concentrations, and the combined effect of titanium nitride's enhanced absorption in the visible-near-infrared band is even better.
[0056] Example 1
[0057] This embodiment discloses a carbon nanotube-titanium nitride composite nanofluid, comprising 10 ppm MWCNT powder, 5 ppm TiN powder, 20 ppm oleic acid, and thermal oil, wherein the outer diameter of the MWCNT is 10~20 nm, the length of the MWCNT is 10~30 μm, and the particle size of the TiN particles is 10~20 nm.
[0058] A method for preparing a carbon nanotube-titanium nitride composite nanofluid includes the following steps:
[0059] (1) Raw material pretreatment: MWCNT powder was ultrasonically cleaned with anhydrous ethanol for 30 min to remove impurities on the surface of MWCNT, and then vacuum dried at 60℃ for 12 h to break up the aggregated MWCNT bundles; TiN powder was washed twice with deionized water and vacuum dried at 60℃ to remove surface oxide impurities and avoid particle agglomeration.
[0060] (2) Base preparation: Add 20mg of oleic acid to 1L of heat transfer oil and stir magnetically for 20min at room temperature until completely dissolved, so that the oleic acid is uniformly dissolved in the heat transfer oil to form an oil phase dispersion base;
[0061] (3) Preparation of MWCNT mother liquor: 10 mg of MWCNT powder from step (1) was added to the oil phase dispersion substrate in step (2) in batches, and MWCNT powder was added in 5 equal amounts. The mixture was stirred for 15 min to allow the MWCNT powder to be initially wetted, and then ultrasonically dispersed in a water bath at 40°C for 40 min to obtain 5 ppm of single pre-dispersed MWCNT mother liquor.
[0062] (4) Compound dispersion: Add 5mg TiN powder to the MWCNT mother liquor in step (3), and add TiN powder in 5 equal portions; first, perform magnetic stirring for 30min to achieve preliminary mixing of TiN particles; then, use a 750W water bath for 20min and a 750W probe for 20min in sequence. The temperature is controlled at 40℃ throughout the water bath and probe ultrasound to prevent the heat transfer oil from deteriorating and the oleic acid from decomposing due to high temperature.
[0063] (5) Degassing and standing: After the probe is sonicated in step (4), it is placed at room temperature in the dark for 30 minutes to degas and remove tiny bubbles in the system, so as to obtain a uniform and stable composite nanofluid.
[0064] (6) Stabilization treatment: After degassing in step (5), the composite nanofluid is sealed and left to stand for 7 days to complete sedimentation screening; unqualified samples with obvious precipitation are removed, and qualified fluid is the final carbon nanotube-titanium nitride composite nanofluid. The carbon nanotube-titanium nitride composite nanofluid is sealed and stored.
[0065] Example 2
[0066] This embodiment discloses a carbon nanotube-titanium nitride composite nanofluid, comprising 10 ppm MWCNT powder, 10 ppm TiN powder, 20 ppm oleic acid, and thermal oil, wherein the outer diameter of the MWCNT is 10~20 nm, the length of the MWCNT is 10~30 μm, and the particle size of the TiN particles is 10~20 nm.
[0067] A method for preparing a carbon nanotube-titanium nitride composite nanofluid includes the following steps:
[0068] (1) Raw material pretreatment: MWCNT powder was ultrasonically cleaned with anhydrous ethanol for 30 min to remove impurities on the surface of MWCNT, and then vacuum dried at 60℃ for 12 h to break up the aggregated MWCNT bundles; spherical TiN nanoparticles were washed twice with deionized water and vacuum dried at 60℃ to remove surface oxide impurities and avoid particle agglomeration.
[0069] (2) Base preparation: Add 20mg of oleic acid to 1L of heat transfer oil and stir magnetically at room temperature for 20min until completely dissolved, so that the oleic acid is uniformly dissolved in the heat transfer oil to form an oil phase dispersion base;
[0070] (3) Preparation of MWCNT mother liquor: 10 mg of MWCNT powder from step (1) was added to the oil phase dispersion substrate in step (2) in batches, and MWCNT powder was added in 5 equal amounts. The mixture was stirred for 15 min to allow the MWCNT powder to be initially wetted, and then ultrasonically dispersed in a water bath at 40°C for 40 min to obtain 5 ppm of single pre-dispersed MWCNT mother liquor.
[0071] (4) Compound dispersion: 10 mg TiN powder is added to the MWCNT mother liquor in step (3), and TiN powder is added in 5 equal portions; first, magnetic stirring is performed for 30 min to achieve preliminary mixing of TiN particles; then, 750 W power water bath ultrasonication is performed for 20 min, and 750 W power probe ultrasonication is performed for 20 min. The temperature is controlled at 40℃ throughout the water bath ultrasonication and probe ultrasonication to prevent the heat transfer oil from deteriorating and the oleic acid from decomposing due to high temperature;
[0072] (5) Degassing and standing: After the probe is sonicated in step (4), it is placed at room temperature in the dark for 30 minutes to degas and remove tiny bubbles in the system, so as to obtain a uniform and stable composite nanofluid.
[0073] (6) Stabilization treatment: After degassing in step (5), the composite nanofluid is sealed and left to stand for 7 days to complete sedimentation screening; unqualified samples with obvious precipitation are removed, and qualified fluid is the final carbon nanotube-titanium nitride composite nanofluid. The carbon nanotube-titanium nitride composite nanofluid is sealed and stored.
[0074] Example 3
[0075] This embodiment discloses a carbon nanotube-titanium nitride composite nanofluid, comprising 10 ppm MWCNT powder, 15 ppm TiN powder, 20 ppm oleic acid, and thermal oil, wherein the outer diameter of the MWCNT is 10~20 nm, the length of the MWCNT is 10~30 μm, and the particle size of the TiN particles is 10~20 nm.
[0076] A method for preparing a carbon nanotube-titanium nitride composite nanofluid includes the following steps:
[0077] (1) Raw material pretreatment: MWCNT powder was ultrasonically cleaned with anhydrous ethanol for 30 min to remove impurities on the surface of MWCNT, and then vacuum dried at 60℃ for 12 h to break up the aggregated MWCNT bundles; TiN powder was washed twice with deionized water and vacuum dried at 60℃ to remove surface oxide impurities and avoid particle agglomeration.
[0078] (2) Base preparation: Add 20mg of oleic acid to 1L of heat transfer oil and stir magnetically at room temperature for 20min until completely dissolved, so that the oleic acid is uniformly dissolved in the heat transfer oil to form an oil phase dispersion base;
[0079] (3) Preparation of MWCNT mother liquor: 10 mg of MWCNT powder from step (1) was added to the oil phase dispersion substrate in step (2) in batches, and MWCNT powder was added in 5 equal amounts. The mixture was stirred for 15 min to allow the MWCNT powder to be initially wetted, and then ultrasonically dispersed in a water bath at 40°C for 40 min to obtain 5 ppm of single pre-dispersed MWCNT mother liquor.
[0080] (4) Compound dispersion: 15mg TiN powder is added to the MWCNT mother liquor in step (3), and TiN powder is added in 5 equal portions; first, magnetic stirring is performed for 30min to achieve preliminary mixing of TiN particles; then, 750W power water bath ultrasonication is performed for 20min, and 750W power probe ultrasonication is performed for 20min. The temperature is controlled at 40℃ throughout the water bath ultrasonication and probe ultrasonication to prevent the heat transfer oil from deteriorating and oleic acid from decomposing due to high temperature;
[0081] (5) Degassing and standing: After the probe is sonicated in step (4), it is placed at room temperature in the dark for 30 minutes to degas and remove tiny bubbles in the system, so as to obtain a uniform and stable composite nanofluid.
[0082] (6) Stabilization treatment: After degassing in step (5), the composite nanofluid is sealed and left to stand for 7 days to complete sedimentation screening; unqualified samples with obvious precipitation are removed, and qualified fluid is the final carbon nanotube-titanium nitride composite nanofluid. The carbon nanotube-titanium nitride composite nanofluid is sealed and stored.
[0083] Example 4
[0084] This embodiment discloses a carbon nanotube-titanium nitride composite nanofluid, comprising 10 ppm MWCNT powder, 20 ppm TiN powder, 20 ppm oleic acid, and thermal oil, wherein the outer diameter of the MWCNT is 10~20 nm, the length of the MWCNT is 10~30 μm, and the particle size of the TiN particles is 10~20 nm.
[0085] A method for preparing a carbon nanotube-titanium nitride composite nanofluid includes the following steps:
[0086] (1) Raw material pretreatment: MWCNT powder was ultrasonically cleaned with anhydrous ethanol for 30 min to remove impurities on the surface of MWCNT, and then vacuum dried at 60℃ for 12 h to break up the aggregated MWCNT bundles; TiN powder was washed twice with deionized water and vacuum dried at 60℃ to remove surface oxide impurities and avoid particle agglomeration.
[0087] (2) Base preparation: Add 20mg of oleic acid to 1L of heat transfer oil and stir magnetically at room temperature for 20min until completely dissolved, so that the oleic acid is uniformly dissolved in the heat transfer oil to form an oil phase dispersion base;
[0088] (3) Preparation of MWCNT mother liquor: 10 mg of MWCNT powder from step (1) was added to the oil phase dispersion substrate in step (2) in batches, and MWCNT powder was added in 5 equal amounts. The mixture was stirred for 15 min to allow the MWCNT powder to be initially wetted, and then ultrasonically dispersed in a water bath at 40°C for 40 min to obtain 5 ppm of single pre-dispersed MWCNT mother liquor.
[0089] (4) Compound dispersion: 20 mg TiN powder is added to the MWCNT mother liquor in step (3), and TiN powder is added in 5 equal portions; first, magnetic stirring is performed for 30 min to achieve preliminary mixing of TiN particles; then, water bath ultrasonication with 750 W power is used for 20 min, and probe ultrasonication with 750 W power is used for 20 min. The temperature is controlled at 40℃ throughout the water bath ultrasonication and probe ultrasonication to prevent the heat transfer oil from deteriorating and oleic acid from decomposing due to high temperature;
[0090] (5) Degassing and standing: After the probe is sonicated in step (4), it is placed at room temperature in the dark for 30 minutes to degas and remove tiny bubbles in the system, so as to obtain a uniform and stable composite nanofluid.
[0091] (6) Stabilization treatment: After degassing in step (5), the composite nanofluid is sealed and left to stand for 7 days to complete sedimentation screening; unqualified samples with obvious precipitation are removed, and qualified fluid is the final carbon nanotube-titanium nitride composite nanofluid. The carbon nanotube-titanium nitride composite nanofluid is sealed and stored.
[0092] Comparative Example 1
[0093] This embodiment discloses a carbon nanotube-titanium nitride composite nanofluid, comprising 10 ppm MWCNT powder, 10 ppm TiN powder, 20 ppm oleic acid, and thermal oil, wherein the outer diameter of the MWCNT is 10~20 nm, the length of the MWCNT is 10~30 μm, and the particle size of the TiN particles is 10~20 nm.
[0094] A method for preparing a carbon nanotube-titanium nitride composite nanofluid includes the following steps:
[0095] (1) Raw material pretreatment: MWCNT powder was ultrasonically cleaned with anhydrous ethanol for 30 min to remove impurities on the surface of MWCNT, and then vacuum dried at 60℃ for 12 h to disperse the aggregated MWCNT bundles; spherical TiN nanoparticles were washed twice with deionized water and vacuum dried at 60℃ to remove surface oxide impurities and avoid particle agglomeration.
[0096] (2) Base preparation: Add 20mg of oleic acid to 1L of heat transfer oil and stir magnetically at room temperature for 20min until completely dissolved, so that the oleic acid is uniformly dissolved in the heat transfer oil to form an oil phase dispersion base;
[0097] (3) Preparation of MWCNT mother liquor: 10 mg of MWCNT powder from step (1) was added to the oil phase dispersion substrate in step (2) in batches, and MWCNT powder was added in 5 equal amounts. The mixture was stirred for 15 min to allow the MWCNT powder to be initially wetted, and then ultrasonically dispersed in a water bath at 40°C for 40 min to obtain 5 ppm of single pre-dispersed MWCNT mother liquor.
[0098] (4) Degassing and standing: The MWCNT mother liquor from step (3) was left to stand at room temperature in the dark for 30 minutes to degas and remove tiny bubbles in the system, thus obtaining a uniform and stable MWCNT nanofluid.
[0099] (5) Stabilization treatment: After degassing in step (4), the MWCNT nanofluid is sealed and left to stand for sedimentation and screening; unqualified samples with obvious precipitation are removed, and qualified MWCNT nanofluid is sealed and stored.
[0100] The difference from Example 1 is that TiN nanoparticles are not added.
[0101] Comparative Example 2
[0102] Pure T66 heat transfer oil fluid.
[0103] The mass fraction of each raw material in Examples 1-4 is shown in Table 1.
[0104] Table 1. Mass fraction of each raw material in Examples 1-4
[0105]
[0106] Figure 1 The images show physical images of carbon nanotube-titanium nitride composite nanofluids after standing for 7 days, as shown in Examples 1-4. No visible precipitation was observed after 7 days of standing.
[0107] Figure 2In Figure 1, A is a TEM image of a nanofluid containing a single multi-walled carbon nanotube, in which the multi-walled carbon nanotube is in an aggregated state; B is a TEM image of a nanofluid containing a single titanium nitride, in which the titanium nitride is in an aggregated state; C is a TEM image of the carbon nanotube-titanium nitride composite nanofluid of the present invention. Compared with A and B, the carbon nanotubes and titanium nitride in Figure C are in a dispersed state.
[0108] Experimental Example 1
[0109] Photothermal conversion experiments were conducted on the carbon nanotube-titanium nitride composite nanofluids of Examples 1-4, the fluid of Comparative Example 1, and the T66 heat-conducting oil fluid of Comparative Example 2.
[0110] 1.1 Fluid absorbance:
[0111] Examples 1-4 and Comparative Document 1 show the absorbance of fluid sunlight at wavelengths of 300–800 nm. See also: Figure 3 At wavelengths of 300-800 nm, the absorbance of Example 4 > the absorbance of Example 3 > the absorbance of Example 2 > the absorbance of Example 1 > the absorbance of Comparative Example 1 > the absorbance of Comparative Example 2.
[0112] 1.2 Fluid transmittance:
[0113] Fluid transmittance at wavelengths of 300–800 nm for Examples 1–4 and Comparative Document 1, see [link to document]. Figure 4 At wavelengths of 300–800 nm, the transmittance of Example 4 > the transmittance of Example 3 > the transmittance of Example 2 > the transmittance of Example 1 > the transmittance of Comparative Example 1 > the transmittance of Comparative Example 2.
[0114] 1.3 Fluid Spectral Absorption Density:
[0115] The spectral absorption densities of the fluids in Examples 1-4 and Comparative Document 1 at wavelengths of 300–800 nm are shown in the attached table. Figure 5 When TiN is added to 20 ppm, its spectral absorption area accounts for 68.7% of the total solar radiation energy according to the standard ASTM G173-03, and its broadband light absorption capacity is significantly better than that of a single-component working fluid.
[0116] 1.4 Fluid Solar Weighted Absorption Rate:
[0117] Fluid solar weighted absorptivity for Examples 1-4 and Comparative Document 1, see [link to document]. Figure 6 With a solar penetration distance of 2-4 cm, the solar weighted absorptivity of Example 4 > that of Example 3 > that of Example 2 > that of Comparative Example 1 > that of Comparative Example 2.
[0118] 1.5 Temperature difference analysis of the fluid photothermal conversion process:
[0119] 1.5.1 Temperature variation characteristics and temperature distribution within the fluid layer of the mixed MWCNT-TiN nanofluid under different TiN mass fractions during illumination, see [reference needed]. Figures 7-10 :
[0120] from Figures 7-9 It can be seen that at the bottom, middle, and top positions, the temperature of all working fluids continuously increases with the increase of irradiation time, and the overall trend shows a rapid increase followed by a gradual slowdown. This is mainly because in the early stage of irradiation, the nanofluid can quickly absorb solar radiation and convert it into heat energy, causing the temperature to rise rapidly; as time goes on, the system temperature gradually increases, the temperature difference between the system and the environment increases, resulting in increased convective and radiative heat loss, and the heating rate gradually slows down.
[0121] The temperature changes at the top, middle, and bottom of the MWCNT–TiN nanofluid mixed under different TiN mass fractions after 1 hour of irradiation are shown in the figure. Figure 10 .from Figure 10 As can be seen, compared with the 10ppm MWCNT nanofluid, the composite nanofluid with added TiN nanoparticles exhibited a higher temperature change throughout the irradiation process. As the TiN mass fraction gradually increased from 5ppm to 20ppm, the temperature rise performance of the nanofluid further improved, with the largest temperature change observed at a TiN mass fraction of 10ppm. After 60 minutes of irradiation, the temperature rises of the 10ppm MWCNT-10ppm TiN composite nanofluid at the top, middle, and bottom were 98.3℃, 96.8℃, and 96.2℃, respectively, while the temperature rises of the 10ppm MWCNT nanofluid were 94.5℃, 93.4℃, and 92.7℃, respectively. This indicates a synergistic absorption effect between TiN nanoparticles and MWCNTs, which can further enhance light absorption and heat accumulation.
[0122] 1.5.2 Temperature field distribution of the collector on the vertical plane during the photothermal conversion process of nanofluids, see [reference]. Figures 11-16 :
[0123] Figures 11-16 In this model, points with the same temperature at the same moment constitute an isothermal surface, which appears as isotherms on the cross-section. Furthermore, the six temperature field distribution diagrams show that the greater the depth of the nanofluid, the denser the distribution of isotherms, indicating a greater temperature difference between the top and bottom nanofluids. At the same fluid depth, the time required for the nanofluid to move from one isotherm to the next during heating gradually increases. This suggests that the rate of temperature increase of the nanofluid decreases with prolonged illumination time, a finding consistent with... Figures 7-10 The temperature change curves of medium-sized nanofluids follow a similar trend.
[0124] Depend on Figures 11-16 As shown in the temperature field, in the initial stage of photothermal conversion, the isotherms inside the collector are sparsely distributed, and the overall heat flux density and heat flux are at a low level, with the horizontal heat flux generally greater than the vertical one. For the composite nanofluids of 10ppmMWCNT-5ppm TiN and 10ppmMWCNT-10ppm TiN, their high transmittance allows radiant energy to penetrate to deeper regions, and the fluids at all depths participate in photothermal conversion, resulting in a small internal temperature difference and therefore a small vertical heat flux. At this point, the overall temperature rise of the fluid has created a significant temperature difference between it and the environment, so the horizontal heat loss dominates. When the TiN concentration increases to 15-20ppm, the fluid extinction coefficient increases significantly, and light energy is concentrated at the surface for absorption, leading to a rapid increase in surface temperature. At this point, the large temperature difference between the surface and the environment means that the horizontal heat flux still dominates, and the thermal localization effect is obvious. In the later stages of photothermal conversion, as irradiation time increases, the isotherm distribution becomes denser, and the overall heat flux within the fluid increases. Furthermore, due to the continuous accumulation of the vertical temperature difference between the surface and deeper fluid layers, the proportion of the vertically downward heat flux driving heat transfer to the deeper layers significantly increases. This is beneficial for storing heat within the fluid, thereby improving the collector's heat storage capacity and overall conversion efficiency. However, the simultaneous increase in horizontal heat flux also exacerbates heat loss to the environment. Therefore, in practical applications, it is necessary to optimize the nanofluid concentration and collector design to find the optimal balance between enhancing bulk heat absorption and suppressing surface heat loss.
[0125] 1.6 Photothermal conversion efficiency of fluids:
[0126] 1.6.1 Comparison of collector efficiencies for hybrid MWCNT-TiN nanofluids, MWCNT nanofluids, and base fluids; see [link to relevant documentation]. Figure 17 :
[0127] from Figure 17 As can be seen, the heat collection efficiency of T66 heat transfer oil, single MWCNT nanofluid, and composite MWCNT-TiN nanofluids with different TiN contents gradually decreases with prolonged irradiation time. This is because during continuous irradiation, the temperature continuously rises, and the temperature difference between the collector and the environment increases accordingly, leading to a continuous increase in convective and radiative heat loss, ultimately resulting in a gradual decrease in heat collection efficiency.
[0128] 1.6.2 Comparison of efficiency of mixed MWCNT-TiN nanofluid and MWCNT nanofluid with base fluid (T66 thermal oil) at irradiation times of 20 min, 40 min, and 60 min, see [link to relevant documentation]. Figure 18 :
[0129] from Figure 18As can be seen, the photothermal conversion efficiency of the composite MWCNT-TiN nanofluid is higher than that of pure heat transfer oil and single MWCNT nanofluid, with the highest photothermal conversion efficiency at a TiN mass fraction of 10 ppm. Compared with the 10 ppm MWCNT nanofluid at 20 min, 40 min, and 60 min, the efficiency of the 10 ppm MWCNT-10 ppm TiN composite nanofluid is increased by 7.9%, 5.4%, and 3.8%, respectively, indicating the effectiveness of the composite MWCNT-TiN in direct absorption solar energy (DASC).
[0130] 1.6.3 The variation of the solar collector's photothermal conversion efficiency with fluid depth after 20 min of illumination for different concentrations of MWCNT-TiN composite nanofluids is shown in [reference]. Figure 19 :
[0131] Figure 19 The black line represents the isoefficiency line, reflecting the relationship between the fluid depth required to achieve a specific efficiency and the concentration of the nanofluid. As shown in the figure, at the same concentration, a higher isoefficiency line indicates a greater required fluid depth, suggesting that nanofluid at a greater depth participates in photothermal conversion and heat storage. When using a base fluid (heat transfer oil) for photothermal conversion, the efficiency at a depth of 3.5 cm is approximately 65.9%. However, the addition of MWCNT and TiN nanoparticles significantly reduces the required fluid depth to achieve the same efficiency. This is attributed to the superior broad-spectrum absorption capacity and photothermal conversion performance of the MWCNT-TiN composite nanofluid. At a depth of 2.5 cm, the efficiency of 10 ppm MWCNT nanofluid is 64.7%, while the efficiency of the 10 ppm MWCNT-10 ppm TiN composite nanofluid increases to 69.4%, indicating that the introduction of TiN enhances the photothermal conversion capacity per unit depth. When the TiN concentration further increases to 15 ppm and 20 ppm, the efficiency at the same depth actually decreases slightly, to 68.2% and 67.1% respectively, showing a non-linear trend of first increasing and then decreasing. This is because when the TiN concentration is 5-10 ppm, the extinction coefficient of the composite nanofluid is moderate, and the radiant energy can be gradually absorbed within a certain depth. All fluid layers participate in photothermal conversion, and the synergistic effect of MWCNT and TiN enhances the broad-spectrum absorption capacity, thus increasing the efficiency with increasing concentration. When the TiN concentration is 15-20 ppm, the transmittance of the nanofluid decreases significantly, and the radiant energy is mainly absorbed by the surface fluid. The surface absorption phenomenon intensifies, and the surface fluid temperature rises rapidly, increasing the heat exchange loss with the external environment, thereby inhibiting further improvement in the overall photothermal conversion efficiency. Therefore, to optimize the performance of direct absorption solar collectors, the nanofluid concentration must be controlled within a certain range and designed in conjunction with the collector's flow channel depth to achieve the optimal balance between enhancing bulk heat absorption and controlling surface heat loss.
[0132] As can be seen from the above, the composite nanofluid of this invention exhibits no precipitation after only 7 days of standing, demonstrating stable properties. The solar weighted absorptivity and photothermal conversion efficiency of Example 2 are higher than those of Example 1.
[0133] The composite nanofluid of Example 2 achieved a solar weighted absorptivity of 94.89% at a 2cm optical path and a photothermal conversion efficiency of 3.8% to 7.9% higher than that of the single MWCNT (Comparative Example 1) fluid during 60min of irradiation.
[0134] The composite nanofluid in Example 3 has higher absorbance, but the surface endothermic effect is aggravated, and the photothermal conversion efficiency is slightly lower than that in Example 2.
[0135] The composite nanofluid in Example 4 has the largest full-spectrum absorption area, accounting for 68.7% of the total solar radiation energy according to the standard ASTM G173-03. Its broadband light absorption capacity is significantly better than that of the fluid heat transfer medium in the comparative example. However, the fluid transmittance is extremely low, and light energy is only absorbed at the surface. The large temperature difference between the surface and the environment leads to increased heat loss, and the photothermal conversion efficiency is lower than that of Examples 1, 2, and 3.
[0136] The fluid in Comparative Example 1 had a solar weighted absorptivity of only 62.38% at a 2cm optical path, and its photothermal conversion efficiency after 60 minutes of irradiation was lower than that of the Example.
[0137] The T66 heat transfer oil in Comparative Example 2 could not completely absorb sunlight at a fluid depth of 10cm, and its photothermal conversion efficiency was far lower than that of the Example and Comparative Example 1.
[0138] The carbon nanotube-titanium nitride composite nanofluid of the present invention has the following beneficial effects:
[0139] 1. Full-spectrum synergistic light absorption significantly improves solar weighted absorptivity:
[0140] MWCNT compensates for absorption in the ultraviolet-visible band, while TiN enhances near-infrared absorption through localized surface plasmon resonance; the two have complementary and superimposed spectra. The optimal ratio is the composite nanofluid of Example 2 (10ppm MWCNT + 10ppm TiN), which achieves a solar weighted absorptivity of 94.89% at a 2cm optical path. The solar weighted absorptivity of the composite nanofluid of Example 2 is much higher than that of the single 10ppm MWCNT fluid in Comparative Example 1, which has a solar weighted absorptivity of 62.38% at a 2cm optical path. When the TiN addition amount in Example 4 is 20ppm, the spectral absorption area accounts for 68.7% of the total solar radiation energy according to the standard ASTM G173-03, and the broadband absorption capacity is significantly better than that of Comparative Example 1.
[0141] 2. Excellent long-term dispersion stability:
[0142] Oleic acid, as an oil-phase compatible dispersant, modifies the surface of MWCNT and TiN particles, weakening the van der Waals aggregation between particles; the fluid product shows no visible precipitation after standing for 7 days, and the absorbance decreases by less than 5% across the entire 300~800nm wavelength range before and after standing, with the absorbance of the highest concentration sample changing by no more than 6%, and can operate stably in the photothermal heat collection system for a long time.
[0143] 3. Photothermal conversion efficiency is significantly optimized, and an optimal ratio window exists:
[0144] The photothermal conversion efficiency of the composite system first increases and then decreases with the amount of TiN added. In the optimal ratio example 2, the photothermal conversion efficiency was increased by 7.9%, 5.4%, and 3.8% respectively under irradiation for 20 min, 40 min, and 60 min compared with the single MWCNT fluid. At low TiN concentration, light energy can penetrate deep into the fluid, and the overall heat storage capacity is strong, avoiding the defects of excessive heat absorption and surge in heat loss on the surface of high-concentration TiN.
[0145] 4. Low raw material cost and strong industrial adaptability:
[0146] It replaces precious metal plasma materials such as gold and silver, using low-cost TiN nanoparticles; the preparation process only involves stirring and ultrasonic conventional chemical operations, without the need for high temperature, high pressure, or complex modification equipment, and can be mass-produced; it is compatible with existing direct absorption solar collectors, and can achieve almost complete solar light absorption with only a 2cm shallow fluid layer, reducing the size of the collector cavity and lowering the equipment manufacturing cost.
[0147] 5. Uniform temperature field distribution and excellent thermal storage performance:
[0148] Adding an appropriate amount of TiN enhances the vertical heat flux of the fluid, allowing heat to be transferred and stored deeper within the collector during the irradiation process. High-ratio TiN only results in localized surface heat absorption. By adjusting the optimal TiN concentration of 10 ppm, the surface heat absorption and deep heat storage can be balanced, reducing the vertical temperature difference of the fluid and minimizing convective and radiative heat loss from the environment.
[0149] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above features with (but not limited to) technical features with similar functions disclosed in this application.
[0150] It should be understood that the sequence number of each step in the invention and embodiments of this application does not absolutely imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The foregoing description of the implementation of this application has been given for illustrative and descriptive purposes. The foregoing description is not exhaustive and is not intended to limit this application to the exact form disclosed. Various modifications and variations may exist based on the above teachings, or various modifications and variations may be derived from the practice of this application. These embodiments were chosen and described to illustrate the principles of this application and its practical application, so that those skilled in the art can utilize this application in various implementations and modifications to suit the specific purpose of the concept. Those skilled in the art will understand that the above-described embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail may be made without departing from the spirit and scope of this application.
Claims
1. A carbon nanotube-titanium nitride composite nanofluid, characterized by, include: The mixture comprises carbon nanotubes, titanium nitride, a dispersant, and a base liquid, wherein the dispersant is modified on the surfaces of the carbon nanotubes and the titanium nitride, and the mass ratio of the carbon nanotubes to the titanium nitride is 2:1 to 4.
2. The carbon nanotube-titanium nitride composite nanofluid according to claim 1, wherein the carbon nanotube-titanium nitride composite nanofluid is prepared by mixing the carbon nanotube and the titanium nitride in a weight ratio of 1: 1 to 1:
10. The mass ratio of the carbon nanotubes to the titanium nitride is 2:
2.
3. The carbon nanotube-titanium nitride composite nanofluid according to claim 1, characterized in that, The carbon nanotubes are single-walled, double-walled, or multi-walled carbon nanotubes; the base liquid is an oily liquid; and the dispersant is oleic acid, stearic acid, or ricinoleic acid.
4. The carbon nanotube-titanium nitride composite nanofluid according to claim 3, characterized in that, The oily liquid is a heat transfer oil with an operating temperature of 250°C or higher.
5. The carbon nanotube-titanium nitride composite nanofluid according to claim 1, characterized in that, The carbon nanotubes have a strip-like structure with an outer diameter of 10-20 nm and a length of 10-30 μm.
6. The carbon nanotube-titanium nitride composite nanofluid according to claim 1, characterized in that, The titanium nitride is in the form of spherical particles with a particle size of 10~20nm.
7. The method for preparing a carbon nanotube-titanium nitride composite nanofluid according to any one of claims 1-6, characterized in that, Includes the following steps: Carbon nanotube powder and titanium nitride particles are prepared for use after surface treatment; The dispersant is dissolved in the base liquid to obtain an oil-phase dispersion substrate; The surface-treated carbon nanotube powder is added to the oil-phase dispersion substrate and mixed and stirred to obtain a carbon nanotube mother liquor; Titanium nitride particles were added to the carbon nanotube mother liquor, and after mixing and stirring, the mixture was allowed to stand in the dark to remove bubbles, thus obtaining a composite nanofluid.
8. The method for preparing a carbon nanotube-titanium nitride composite nanofluid according to claim 7, characterized in that, The surface treatment includes: the carbon nanotube powder being washed with alcohol and dried; and the titanium nitride particles being washed with water and dried.
9. The method for preparing a carbon nanotube-titanium nitride composite nanofluid according to claim 7, characterized in that, After the titanium nitride particles are added to the carbon nanotube mother liquor and mixed and stirred, they are subjected to water bath ultrasonic dispersion and probe ultrasonic dispersion, and then subjected to light-proof static degassing. The ultrasonic power of the water bath ultrasonic dispersion and the probe ultrasonic dispersion is 600-800W, and the water bath temperature of the water bath ultrasonic dispersion is 45~50℃.
10. The application of a carbon nanotube-titanium nitride composite nanofluid as described in any one of claims 1-6 in a direct absorption solar collector photothermal conversion system.
